Buckling of cold-stretched cylindrical vessels under external pressure: Experimental and numerical investigation. (October 2018) - Zhang, Zekun; Hui, Peizi; Gu, Chaohua; Xu, Ping; Wu, Yingzhe; Hua, Zhengli
Abstract: Cold-stretching is an important lightweight technology for reducing cost of cryogenic vessels, which are widely used for storing liquefied gas. This paper studied the influence of cold-stretching on the buckling behavior of cylindrical vessels with different initial out-of-roundness under external pressure. Buckling pressures, strains, and buckling modes of cylindrical vessels were obtained from experiments. A 3D laser scanner was used to obtain the complicated geometry of the vessels before and after cold-stretching. Based on the 3D scanned geometry, we performed FEA to evaluate the buckling pressures, which resulted in a good agreement with the experimental values. The effects of cold-stretching on buckling are discussed based on four factors: out-of-roundness, thickness, diameter and yield strength. Firstly, buckling of cylindrical vessels is elastic buckling in our case, so yield strength has no influence on buckling pressure. Secondly, the negative effect of diameter-thickness ratio increasing was proved to be slight (within 3.3%) in our case. Finally, buckling pressure increased after cold-stretching because out-of-roundness decreased. Experiments showed that buckling pressures were enhanced by 10.8% and 13.6% after cold-stretching for long and short cylindrical vessels with 1.9% and 1.6% in out-of-roundness. Highlights: Twelve thin-walled cylindrical vessels subjected to external pressure were tested. Strains, buckling pressures, and buckling modes were obtained. A 3D laser scanner was used to measure the shapes of the cylindrical vessels. Finite element analysis was carried out based on the measured shapes. The influence of cold-stretching on buckling of cylindrical vessels with out-of-roundness was studied.